Indignados no cenário da crise: movimentos sociais antissistêmicos no Século XXI e a emergência da cultura política em rede - Kaminski, Ricardo da Silva (2014)
This dissertation substantiates the thesis that networks of social movements that emerged in the second decade of the twenty-first century – in the scene of the crisis which intensified since 2008 - are setting up a network political culture, based on antis-systemic cultural practices. Such networks of political constellations, characteristics of cyberculture, seek to redefine the parameters of the political in the dominant culture of the capitalist system, developing rhizomatic strategies of cultural recoding, in order to reconfigure thus the asymmetrical relations of power and the limits of representative democracy in contemporary society. The research, conducted in the period from 2011 to 2013, was developed from a netnography approach with Occupy Wall Street movement, more specifically with one of its political constellations, the Novads. In order to configure the features of network political culture, sought to establish correlations between common cultural practices, in their interconnections with other movements, such as Ocupa Sampa in Brazil and the Spanish Indignants movement. The worldwide network that connects individual and social groups by cyberspace configures interpersonal links to consolidate new forms of existence: symbolic webs and different political and cultural values are created and strengthened in connections with other movements in a multiplicity of actors on cultural and institutional spaces, within and across national borders. Emerges from this lively and rebellious network an anti - systemic political culture forged in the practices and interpersonal and organizational knowledge. Emerges from this lively and rebellious network an anti-systemic political culture forged in the practices and interpersonal and organizational knowledge.